2016
DOI: 10.3847/0004-637x/819/1/31
|View full text |Cite
|
Sign up to set email alerts
|

LATE-TIME PHOTOMETRY OF TYPE IA SUPERNOVA SN 2012cg REVEALS THE RADIOACTIVE DECAY OF 57Co

Abstract: Seitenzahl et al. have predicted that roughly three years after its explosion, the light we receive from a Type Ia supernova (SN Ia) will come mostly from reprocessing of electrons and X-rays emitted by the radioactive decay chain 57 Co→ 57 Fe, instead of positrons from the decay chain 56 Co→ 56 Fe that dominates the SN light at earlier times. Using the Hubble Space Telescope, we followed the light curve of the SN Ia SN 2012cg out to 1055 days after maximum light. Our measurements are consistent with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 63 publications
10
103
2
Order By: Relevance
“…For a comprehensive discussion, the results from other studies such as the deep radio observations of Chomiuk et al (2015), the detection of blueshifted Na i D (Maguire et al 2013) and the late-time photometry observations (Graur et al 2016) for SN 2012cg are also included in this table.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For a comprehensive discussion, the results from other studies such as the deep radio observations of Chomiuk et al (2015), the detection of blueshifted Na i D (Maguire et al 2013) and the late-time photometry observations (Graur et al 2016) for SN 2012cg are also included in this table.…”
Section: Discussionmentioning
confidence: 99%
“…To place strict constraints on the properties of CSM and the observable signatures of the SN shock interacting with the CSM, detailed numerical hydrodynamical simulations for the interaction between the blast wave of the SN and CSM/ISM are required, coupled with different explosion models and the detailed pre-SN massloss history, i.e., different configurations of outflow material around progenitor systems. In addition, (Graur et al 2016) suggested that the decay of 57 Co and 55 Fe produced from current modelling for the two CO WDs merger model have difficulties in explaining the slow-down decline light curve of SN 2012cg at late times. How- ever, they also pointed out that a similar behavior of the late-time light curve of SN 2012cg can be explained by a light echo, which requires future follow-up observations for further confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations